Dynamic Linear Interdependence between International Trade and Macroeconomic Stability in Nigeria: A Vector Error Correction Modelling. - Tuaneh, Godwin Lebari; Essi, Isaac Didi; Ozigbu, C Johnbosco (Archives of Business Research, 2021)
Causal relationships are often treated erroneously in isolation as a single equation without the consideration of the endogeneity of right-hand side variables and also without recourse to the presence of co-integration. This study modelled and estimated the dynamic linear interdependence between international trade and macroeconomic stability in Nigeria. The specific objectives were to, establish the trend of the study variables, model and estimate the interdependence existing among total export, total import, exchange rate, and inflation rate, determine the significant causalities and summarize the causal channels among the study variables. The study used the quasi-experimental design. Monthly time series data on all the variables, which spanned from January, 2000 to June, 2019 were sourced from the Central Bank of Nigeria Statistical Bulletin. Appropriate models were specified in line with the objectives. The study used the Vector Error Correction Models, the pre and post-diagnostic tests were also conducted. The unit root test results showed that the variables were integrated of order one [I(1)]. The co-integration test results showed 1 co-integrating equation and VAR lag length selection criteria choose lag 3. The Vector Error Correction Result showed that inflation rate was the most explained by variations in the independent variables (R2 =73.4%) while exchange Rate was the least explained (R2 =18.8%), the total export model had R2 = 53.8% and total import model had (R2 =59.2%. Significant bi-directional causality was found between total export and inflation rate, and also between total import and inflation rate. There was also significant joint causality on total import and also on exchange rate. The post test showed that the models were stable. It was recommended that the right-hand side variables should be tested for endogeneity before concluding on single or system equation. It was also recommended that policies to check inflation rate should consider possibility of shocks to international trade.